PREVALENCE OF CARDIOVASCULAR DISEASE RISK FACTOR AMONG BAHRAINI ADULTS: A PILOT STUDY - Musaiger, A.O.; Al-Roomi., K.A. (Emirates Journal of Food and Agriculture, 2017)
Please see the scanned pdf version in full text